2007
DOI: 10.1021/jf063764s
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Pesticide Environmental Fate and Exposure Assessments

Abstract: Globalization of markets and the growing world population increase threats of invasive and exotic species and place greater demands on food and fiber production. Pest management in both agricultural and nonagricultural settings employs established practices and new biological, chemical, and management technologies. Pesticides are an essential tool in integrated pest management. Without pesticides a significant percentage of food and fiber crops would be lost, infectious diseases would increase, and valuable na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 57 publications
0
46
0
7
Order By: Relevance
“…Furthermore, vitamin C has been shown to increase the activity of Paraoxonase I (PON I) (Jarvik et al, 2002), an arylesterase, synthesized primarily n the liver and is secreted into the plasma, where it is exclusively bound to High-Density Lipoprotein (HDL) particles containing apoA-I and apoA-j (Kujiraoka et al, 2006), which may have contributed to its antiatherogenic effect. Besides detoxificating OPs, PON1 displays at least two other very important functions including the prevention of unsaturated lipid oxidation and decomposition of lipid peroxidation products of oxidized LDL and HDL in the plasma (Mackness et al, 1998;Shih et al, 1998;Sozmen et al, 2002;Rice et al, 2007). PON1 may also confer protection against damages of vessel wall by antioxidation and destroying oxidative productions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vitamin C has been shown to increase the activity of Paraoxonase I (PON I) (Jarvik et al, 2002), an arylesterase, synthesized primarily n the liver and is secreted into the plasma, where it is exclusively bound to High-Density Lipoprotein (HDL) particles containing apoA-I and apoA-j (Kujiraoka et al, 2006), which may have contributed to its antiatherogenic effect. Besides detoxificating OPs, PON1 displays at least two other very important functions including the prevention of unsaturated lipid oxidation and decomposition of lipid peroxidation products of oxidized LDL and HDL in the plasma (Mackness et al, 1998;Shih et al, 1998;Sozmen et al, 2002;Rice et al, 2007). PON1 may also confer protection against damages of vessel wall by antioxidation and destroying oxidative productions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, models such as Screening Concentration In GROund Water (SCI-GROW), the Pesticide Leaching U.S. (PLUS) and PRZM-Exposure Analysis Modelling System (EXAMS) model are used for estimating groundwater concentrations and for registration of agrochemicals (Rice et al 2007).…”
Section: W Utembe and M Gulumianmentioning
confidence: 99%
“…It is undeniable that the contribution of pesticides has increased the agricultural production over the past decades, but along with its advantages, there are environmental problems associated with pesticide use (Lefebvre et al, 2015;Pimentel et al, 2005;Waterfield and Zilberman, 2012). These problems are often a consequence of the movement of these chemicals to unwanted zones, which represents a potential risk for non-target organisms including human beings (Rice et al, 2007). In this regard, a number of recent monitoring studies have shown the presence of pesticides in soil, sediments, and surface and ground waters.…”
Section: Introductionmentioning
confidence: 99%